PERLINDUNGAN HUKUM TERHADAP HAK-HAK TERSANGKA DALAM PROSES PENYIDIKAN PERKARA TINDAK PIDANA PENGEROYOKAN YANG DILAKUKAN SECARA BERSAMA-SAMA - Laia, Kristinus (LPPM Universitas Nias Raya, 2025)
Legal protection is an effort to protect the government or authorities with a number of existing regulations. In this research, the problem formulation is how the law protects the rights of suspects in the process of investigating cases of criminal acts of assault which are carried out jointly (decision study 475 K/Pid/2018). Investigators violated the suspect's rights during the investigation into decision Number 475 K/Pid/2018. The type of research used is normative legal research using the statutory approach, case approach and analytical approach. Data collection was carried out using primary data, secondary data and tertiary data. The data analysis used is descriptive qualitative analysis and conclusions are drawn using a deductive method. Based on research findings and discussions, it can be concluded that legal protection for suspects' rights has been regulated in statutory regulations in accordance with those contained in the Criminal Procedure Code contained in Articles 50-68, Law Number 39 of 1999 concerning Human Rights, Laws Law Number 48 of 2009 concerning Judicial Power and National Police Chief Regulation Number 14 of 2012 concerning Management of Criminal Investigations. In the event of a violation of a suspect's rights, especially a violation regarding not being given the right to be accompanied by a legal advisor, the investigation report report and the indictment from the public prosecutor cannot be accepted or are null and void by law. The author advises investigators in the process of investigating a case to respect and fulfill the suspect's rights in accordance with applicable regulations. Before an investigation is carried out, the investigator first informs the suspect about his rights as a suspect, so that the suspect's rights can be fulfilled legally. It is also hoped that investigators will be more professional and pay attention to article 56 of the Criminal Procedure Code regarding the obligation of a suspect to be accompanied by a legal advisor if the threat of punishment is more than five years.